Pattern of acceptability to yellow fever vaccination among skilled and unskilled workers in selected African countries - Enitan, Seyi Samson; Yomi, Akele Richard; Ezigbo, Eyiuche Doris; Adejumo, Esther Ngozi; Abbas, Kirellos Said; Elrufai, Rawan Raad Hassan; Umukoro, Solomon; Laura, Tsague Metago Causette; Eke, Samuel Sunday; Aladenika, Seto Tunrayo; Durosinmi, Abiodun Emmanuel; Itodo, Grace Eleojo; Osakue, Eguagie Osareniro; Effiong, Effiong Joseph; Abubakar, Nafisat Eleojo; Ohanu, Ernest Chiuike; Sudan, Gbise Daniel; Udeh, Emmanuel Ochigbo; Oyekale, Adesola Oyekunle; Olorunnisola, Imoleayo Elijah (School of Medicine, Universitas Syiah Kuala, 2023)
Yellow fever still represents a major public health threat in Africa largely due to inadequate vaccine supply, insufficient vaccine coverage, increase in people without of vaccination living in endemic areas and occupation of individuals. The aim of this study was to assess the acceptability to yellow fever vaccination among skilled and unskilled workers in selected African countries. This cross sectional online survey was carried out between 19 January 2022 and 31 December 2022, in five African countries (Cameroon, Egypt, Nigeria, Sudan and the Gambia). The responses to the survey were collected by Survey Monkey and the links were distributed via Facebook, Twitter, and WhatsApp. Data were collected using self-administered structured questionnaire, and analysed. A total of 1340 respondents (601 skilled workers, 739 unskilled workers) participated in the survey of which 616 of them indicated had yellow fever vaccination. Proportion of the unskilled workers with history of vaccination was less than those of the skilled workers (35.5% vs 58.9%). Location (OR=31.04, p=0.000), age (OR=146.95, p=0.001), religion (OR=24.42, p=0.012), education (OR=116.41, p=0.001), marital status (OR=68.83, p=0.001) and monthly household income (OR=87.62, p=0.001) were significantly associated with acceptance to receive YF vaccine. In addition, more of the skilled workers were very willing to receive the YF vaccine compared to their unskilled counterparts (p0.001). This study suggests that unskilled workers are less likely to be vaccinated against yellow fever than skilled workers, hence the need for strategic public health interventions to reach this category of people in the society.